Viral and immunological markers of HIV-associated Kaposi sarcoma recurrence. - Owen Ngalamika; Marie Claire Mukasine; Musonda Kawimbe; Faheema Vally (PLoS ONE, 2021)
Kaposi sarcoma (KS) is an AIDS-defining angio-proliferative malignancy highly prevalent in Sub-Saharan Africa. The main objective of this study was to determine the factors associated with recurrence of HIV-associated KS. We recruited a cohort of individuals on antiretroviral therapy who were in remission for HIV-associated KS after undergoing cytotoxic cancer chemotherapy. Collected variables included sociodemographic and clinical parameters, cytokines and chemokines, HIV viral loads, and CD4 counts. Compared to individuals who had KS recurrence, IL-5 was significantly higher at time of follow-up in individuals who had sustained remission (22.7pg/ml vs. 2.4pg/ml; p = 0.02); IL-6 was significantly higher at baseline and time of follow-up in individuals who had sustained remission, (18.4pg/ml vs. 0pg/ml; p = 0.01) and (18.0pg/ml vs. 0.18pg/ml; p = 0.03) respectively; IP-10 was significantly lower at baseline and at time of follow-up in individuals who had sustained remission, (534pg/ml vs. 920pg/ml; p = 0.04) and (446pg/ml vs.1098pg/ml; p = 0.01) respectively; while HIV viral load was significantly lower at baseline and at time of follow-up in individuals who had sustained remission, (0copies/ml vs. 113copies/ml; p = 0.004) and (0copies/ml vs. 152copies/ml; p = 0.025) respectively. Plasma levels of IL-5, IL-6, and IP-10 are associated with recurrence of HIV-associated KS, while persistently detectable HIV viral loads increase the risk of KS recurrence.